2022
DOI: 10.1186/s12974-022-02477-z
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, an endogenous hormone, modulates Th17 cells via the reactive-oxygen species/TXNIP/HIF-1α axis to alleviate autoimmune uveitis

Abstract: Background Melatonin, an indoleamine produced by the pineal gland, plays a pivotal role in maintaining circadian rhythm homeostasis. Recently, the strong antioxidant and anti-inflammatory properties of melatonin have attracted attention of researchers. We evaluated the therapeutic efficacy of melatonin in experimental autoimmune uveitis (EAU), which is a representative animal model of human autoimmune uveitis. Methods EAU was induced in mice via im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…The impaired clinical recovery in both acute and repair phases of colitis in mice treated with MLT could be linked to the increase in circulating leukocyte and TNF production in the colon, despite reduced IL-17 cytokine, which is fundamental for gut immunity in the control of bacteria burden [ 9 ]. Corroborating our data, MLT was able to inhibit the differentiation of Th17 cells in an experimental model of necrotizing enterocolitis [ 37 ] and, in autoimmune uveitis, MLT suppressed Th17 differentiation through the reactive-oxygen species–TXNIP-HIF1α axis [ 38 ]. On the other hand, cytokines with an inflammatory profile intensify mucosal effector responses, though a consequent deterioration in the intestinal lamina propria due to excessive inflammation may occur [ 39 ].…”
Section: Discussionmentioning
confidence: 55%
“…The impaired clinical recovery in both acute and repair phases of colitis in mice treated with MLT could be linked to the increase in circulating leukocyte and TNF production in the colon, despite reduced IL-17 cytokine, which is fundamental for gut immunity in the control of bacteria burden [ 9 ]. Corroborating our data, MLT was able to inhibit the differentiation of Th17 cells in an experimental model of necrotizing enterocolitis [ 37 ] and, in autoimmune uveitis, MLT suppressed Th17 differentiation through the reactive-oxygen species–TXNIP-HIF1α axis [ 38 ]. On the other hand, cytokines with an inflammatory profile intensify mucosal effector responses, though a consequent deterioration in the intestinal lamina propria due to excessive inflammation may occur [ 39 ].…”
Section: Discussionmentioning
confidence: 55%
“…Melatonin is produced from the pineal gland and, to some extent, from the retina [13]. It has antioxidant functions and a major role in neurovascular and cardiovascular diseases [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin also increases the number of CD4 + FOXP3 + Treg cells and the surface expression of FOXP3, as well as decreases the production of Th2 cytokines in patients with systemic lupus erythematosus 60 . A recent study suggests that melatonin facilitates Treg cell differentiation in autoimmune diseases via ROS/thioredoxin binding protein (TXNIP)/HIF‐1α pathway 61 . In addition, recent studies have shown that melatonin enhances the differentiation of Treg cells via the AMP‐activated protein kinase (AMPK)/LINC01515/SIRT1 axis in necrotizing enterocolitis in human 62,63 .…”
Section: Melatonin Modulates Food Allergy Through the Immune System: ...mentioning
confidence: 99%
“…60 A recent study suggests that melatonin facilitates Treg cell differentiation in autoimmune diseases via ROS/thioredoxin binding protein (TXNIP)/HIF-1α pathway. 61 In addition, recent studies have shown that melatonin enhances the differentiation of Treg cells via the AMP-activated protein kinase (AMPK)/LINC01515/ SIRT1 axis in necrotizing enterocolitis in human. 62,63 However, the effects of melatonin in cancer models are inconsistent compared to that in the inflammation models.…”
Section: Melatonin Regulates Oral Tolerance Via Tregsmentioning
confidence: 99%